Development of a Graphical User Interface for Aircraft Maintenance - Pousette, Sara; Wiik, Petra (2014)
The project was initiated by both Saab Support and Services and the Division of Operation Maintenance Engineering at Luleå University of Technology. It has been carried out as a Bachelor thesis in Industrial Design Engineering at Luleå University of Technology. The project’s aim is to deliver a graphical user interface concept for aircraft maintenance consisting of pictures visualized in Photoshop. The graphical design has the objective to be user friendly, simple, and fast. Since Saab Support and Services is the client the interface will be based on their graphical profile.The target group is aircraft technicians and mechanics that work with Saab aircraft, such as, JAS 39 Gripen. Today the main issues are the large amount of printed out paper from the manual on the computer, insufficient links in the manual, and physical distance between different information sources.In order to develop an interface, theory concerning areas like the design process, generally about aircraft maintenance, design and usability theory, human factors, tablets, and hierarchies was investigated. To gain further knowledge of the context in which the interface will be implemented a visit to the Norrbotten Wing F21 was carried out. During the visit observations and interviews were conducted to gather information about issues and wants.From the issues and wants a product specification took shape. In the idea development a hierarchy of relevant information was formed. In the concept development a first concept was designed through a discussion. The concept was then evaluated by the methods Cognitive Walkthrough and Paper Prototyping, which led to design changes. A detail development was then carried out where colors, icons, fonts, and shapes were decided. A second visit at F21 was also conducted to evaluate the concept.The result is a graphical user interface concept consisting of the pages manual, report, work order, history, specifications, and flight info. To reach these information sources the user must first login and then choose an ...